The Palgrave Centenary Companion to Principia Mathematica - Linsky, Bernard. author. aut Link
XXVII, 458 p.
Keywords: To mark the centenary of the 1910 to 1913 publication of the monumental Principia Mathematica by Alfred N. Whitehead and Bertrand Russell, this collection of fifteen new essays by distinguished scholars considers the influence and history of PM over the last hundred years.